The Role of Islamic Higher Education in Promoting Peace: A Case Study of Fatoni University, Thailand - Solihah Hayeesama-ae (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Being in the contemporary world of today, Islamic education has been challenged in promoting peace, particularly in the context of Muslim minority. The study employs qualitative research methodology to find out the role of Islamic education in promoting peace in a society: A study of Fatoni University, Thailand. This paper reveals that Islam is the religion of peace. Islam considers peace as the top of believe principles and the highest goal of worship and honor God (Allah).Thus, peace is as the ultimate goal of man living both in this world and the Hereafter. Islam prescribes peace in all the system of human life. Through Islamic education system, peace could be built, promoted, and well-functioning at a level of an individual, family, communities, a country, and Ummah as the universal entity. The aims and objectives of Islamic education are the creation a perfect man, who plays the role as a good servant and vicegerent on the earth (Khalifah) and be blessed in this world and the Hereafter; and lead to the construction of a good society based on Islamic teachings. Fatoni University, an Islamic higher educational institute in Thailand, has played its vital role in providing integrated Islamic education and promoting peace. It employs the integrated Islamic curriculum and co-curriculum in preparing its staff and students for building peace. The university can well-functioning in promoting peace through its various roles: the role of the rector and staff, students and alumni, Assalaam Institute, Majlis Ilmi, Maal-Qur’an, Madinah Al-Salaam and Waqaf foundation.The study gives some suggestions for the university to make a more proactive contribution to promote peace in the contemporary context of the society.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//